Pudd'nhead Wilson and those extraordinary twins - Clemens, Samuel Langhorne; Berger, Sidney E. (New York : W.W. Norton & Company, Inc., 1980)
A slave of mixed blood substitutes her son with her master's son.
The text of Pudd'nhead Wilson -- The text of those extraordinary twins -- Textual introduction and tables of variants -- Criticism -- Critical essay.
Includes bibliographical references.
Keywords: LITERARY FICTION